Effect Of Independent Commissioners’ Board, Profitability And Sales Growth On Tax Avoidance - Yuni Astuti; Agus Munandar (Moneter: Jurnal Keuangan dan Perbankan, 2026)
The study examine independent commissioners’ board, profitability, and sales growth influence on tax avoidance practices within Retail Companies listed on IDX in 2018-2024. The quantitative approach employed using panel data from a sample of 119 published retail companies. The analysis is conducted through a series of statistical tests: descriptive analysis, model selection tests, classical assumption and hypothesis test to determine statistical significance. Simultaneously, the independent commissioners’ board, profitability, and sales growth have a significant effect on tax avoidance. However, partial testing reveals a more nuanced outcome: only the independent commissioners’ board significantly positive affect tax avoidance. In contrast, profitability and sales growth do not show a significant partial influence. Independent commissioners’ boardhave a greater affect on tax avoidance than on financial performance. Oversight should focus on the effectiveness of these boards. The specific empirical evidence from retail sector in an emerging market (Indonesia), covering an extensive seven-year period (2018-2024). It contributes to corporate governance and tax literature through dominant role of the board of commissioners over traditional financial determinants in the context of tax avoidance, offering a distinct perspective for both academia and industry practitioners.